MEDIA-NEED ASSESSMENT FOR CHILDREN WITH LEARNING DISABILITIES: A CASE STUDY ON SCAFFOLDING CHILDREN WITH DYSGRAPHIA IN INCLUSIVE SCHOOLS - Gunarhadi; Hremawan; Mahardika; Dewi Sri Rejeki; Hanafi Yasin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Abstract: This research aims at (1) identifying the characteristics of handwriting difficulties in inclusive schools, (2) assessing the types of the intervention of handwriting difficulties, (3) adjusting media utility to the types of handwriting difficulties.This research is an explorative case study involving teachers, therapists, and children with handwriting problems assigned through a snowball sampling technique. Data was collected from the interview, observation, and children work in writing. While observation is conducted to explore the children’ process of writing, the interview is used to get the information from the teachers on the children’ difficulties found in the children work of writing. The data were analyzed by qualitative descriptive on the types of writing problems and the use of utilities for scaffolding. The research concludes that (1) there is a big number of children with dysgraphia, (2) children with dysgraphia need scaffolding through different ways of intervention, (3) the utility of handwriting medium needs adjustment on the individual basis of scaffolding.